Pendampingan Pemberdayaan Guru Pendidikan Agama Islam Dalam Implementasi Pembelajaran Abad 21 - Ansori Muhamad (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2023)
This training in the form of community service aims to provide detailed guidance on designing and developing a 21st century learning in the form of e-learning. Train and prepare the latest instructional in e-learning design orientation and provide basic concepts and information about the processes and basic competencies that play a role in e-learning. Designing and managing e-learning is a new skill in the 21st century that teachers must have. The activity method used is training, mentoring, implementation, and evaluation. Participants in the training and mentoring activities were Islamic Religious Education (PAI) teachers at the Al-Qodiri Jember Middle School Plus (SMP Plus). Data in the form of observations and questionnaires were analyzed descriptively. The result of training and mentoring is that teachers are able to use e-learning well. Teachers can create learning spaces in e-learning that contain student teaching materials. The implementation of e-learning in each school still has limited facilities and infrastructure. The results of the questionnaire responses showed a positive response to the 21st century training and service learning activities.